Organo main group chemistry - Akiba, Kinʼya, 1936- (Wiley, 2011)
"This book will capture the essential scope of organic chemistry of all main group elements and covers all main group elements dealing with syntheses and reactions of their organic compounds. While organic compounds of second row elements centered at carbon are the major components of animals and plants, those of the third row and below are also important and have unique roles which this book discusses. The first eight chapters are arranged according to the periodic table, starting with the role of lithium and magnesium cations (positively charged ions) in synthesis to fluorine and iodine compounds. The last four chapters deal with modern topics that were selected on the basis of unique characteristics of main group elements compared to the carbon (i.e. main group element effect is placed as the central idea to arrange and unify.)"--